Social Exchange and Common Agency in Organizations - R Dur; Hein J. Roelfsema (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2006)
We study the relation between formal incentives and social exchange in organizations where employees work for several managers and reciprocate to a manager's attention with higher effort. To this end, we develop a common agency model with two-sided moral hazard. We show that when effort is contractible and attention is not, the first-best can be achieved through bonus pay for both managers and employees. When neither effort nor attention are contractible, an `attention race' arises, as each manager tries to sway the employee's effort his way. While this may result in too much social exchange, the attention race may also be a blessing because it alleviates managers' moral-hazard problem inattention provision. Lastly, we derive the implications of these contract imperfections for the optimal number of managers that share one employee.
Keywords: 330; social exchange; reciprocity; incentive contracts; common agency; organizational design